Does the Cerebral Cortex Exploit High-Dimensional, Non-linear Dynamics for Information Processing? - Singer, Wolf; Lazar, Andreea (Frontiers in Computational Neuroscience, 2016)
The discovery of stimulus induced synchronisation in the visual cortex suggested the possibility that the relations among low-level stimulus features are encoded by the temporal relationship between neuronal discharges. In this framework, temporal coherence is considered a signature of perceptual grouping. This insight triggered a large number of experimental studies which sought to investigate the relationship between temporal coordination and cognitive functions. While some core predictions derived from the initial hypothesis were confirmed, these studies, also revealed a rich dynamical landscape beyond simple coherence whose role in signal processing is still poorly understood. In this paper a framework is presented which establishes links between the various manifestations of cortical dynamics by assigning specific coding functions to low dimensional dynamic features such as synchronized oscillations and phase shifts on the one hand and high dimensional non-linear, non-stationary dynamics on the other. The data serving as basis for this synthetic approach have been obtained with chronic multisite recordings from the visual cortex of anesthetized cats and from monkeys trained to solve cognitive tasks. It is proposed that the low dimensional dynamics characterized by synchronized oscillations and large-scale correlations are sub-states that represent the results of computations performed in the high dimensional state space provided by recurrently coupled networks.